Facile synthesis of carbon microspheres/tin ethylenediamine tetramethylene phosphonate hybrid for improving the mechanical, flame‐retardant, and thermal properties of epoxy resin. (29th March 2021) - Wang, Wenduo; Wang, Zhengzhou
Abstract : A botryoidal carbon microspheres/tin ethylenediamine tetramethylene phosphonate hybrid (CMS@TETP) was fabricated via a self‐assembly method and was applied to modify epoxy resin (EP) in order to simultaneously improve its mechanical, flame‐retardant, and thermal properties. The mechanical tests' results show that the addition of 1.0 wt% CMS@TETP endows EP with an increase in tensile and impact strengths of 24.4% and 23.1%, respectively, relative to the values of pure EP. The cone calorimeter test results reveal that CMS@TETP has better flame retardancy in EP than either CMS or TETP at the same loading level. In comparison with those of pure EP, the mean heat release rate, peak heat release rate, total heat release, and effective heat of combustion of the EP composite containing 3.0 wt% CMS@TETP (EP/CMS@TETP‐3) are respectively reduced by 49.5%, 59.1%, 47.0%, and 46.1%. The glass transition temperatures of EP/CMS@TETP composites are slightly increased than that of pure EP, indicating an increase in the thermal resistance. Thermogravimetric analysis results provide evidence that CMS@TETP has good char‐forming capacity in EP.